Efeitos hipoalgésicos da combinação entre a estimulação elétrica nervosa transcutânea e manipulação articular cervical em participantes saudáveis: ensaio controlado aleatorizado - Telles, Jonathan Daniel (Universidade Federal de São Carlos, 2019)
Introduction: Transcutaneous electrical nerve stimulation (TENS) and joint manipulation (JM) are often used to treat pain. TENS and MA when applied in healthy participants increase the hypoalgesic effect, however, it is not yet known whether both interventions applied in an associated way may produce a greater hypoalgesic effect. Objectives: To compare the hypoalgesic effects of isolated or combined use of TENS and cervical JM in healthy subjects. Methods: A hundred and forty-four healthy patients aged 18 to 30 years old were randomly assigned to four groups: active TENS + active JM; active TENS + placebo JM; placebo TENS + active JM; placebo TENS + placebo JM. Active TENS or placebo was applied to the dominant forearm with a frequency of 100 Hz, pulse duration of 100 µs for 20 minutes. JM was applied to the C6-7 segments.The pain pressure thershold (PPT) was measured pre- and post-intervention and post- 20 minutes using a digital algometer in the dominant side of the forearm (segmental) and tibialis anterior (extrasegmental). Data analysis was performed using the Kolmogorov-Smirnov test and two-way Anova, followed by Tukey’s post hoc test. Significance differences were considered at p<0.05. Results: There was statistically significant difference for the forearm in relation to time (p= 0.001) and to interaction between time and group (p= 0.002). Active TENS + active JM increased the hypoalgesic effect compared to active TENS + placebo JM (difference= 14,9 Kpa, 95% confidence interval= 5,74 to 21,14, p= 0.002), placebo TENS + active JM (difference= 16,6 Kpa, 95% confidence interval= 7,49 to 25,89, p= 0.001) and placebo TENS + placebo JM (difference= 31,1 Kpa, 95% confidence interval= 21,96 to 40,36, p= 0.001). For the extra-segmental stimulation, there was a statistically significant difference in relation to time (p= 0.001) and to interaction between time and group (p= 0.001). Active TENS + JM had greater hypoalgesic effect compared to active TENS + placebo JM (difference= 8,08 Kpa, 95% confidence interval= 0,64 to 15,51, p = 0.033), placebo TENS + active JM (difference= 11,7, Kpa, 95% confidence interval= 4,34 to 19,21, p= 0.002) and placebo TENS + placebo JM (difference= 15,1, Kpa, 95% confidence interval= 7,75 to 22,63, p= 0.001). Conclusion: TENS and MA cause hypoalgesia and when applied in an associated way, increase the threshold of segmental and extra-segmental pain in healthy participants.
Hypoalgesic effects of the combination between transcutaneous electrical nerve stimulation and cervical joint manipulation in healthy participants: randomized controlled trial
Keywords: Analgesia; Manipulação da coluna cervical; Limiar de dor; Estimulação elétrica nervosa transcutânea; Analgesia; Cervical joint manipulation; Pain threshold; Transcutaneous electrical nerve stimulation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL